Development of Picture Book Learning Media to Improve Writing Potery Skill Based on Local Culture - Bambang Sulistyo; Nur Shabrina Reznani; Nurhasanah Nurhasanah (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to describe the results of developing learning media in the form of a picture book of poetry writing material based on local culture for class VIII students of SMP Negeri 2 Baturaja. The type of research used is Research and Development (R & D). The model used is ADDIE. Data collection techniques in the form of questionnaires, interviews, and tests. Furthermore, the data analysis technique is descriptive statistical analysis technique. The results of the research and discussion showed that the eighth grade students of SMP Negeri 2 Baturaja needed learning media to write poetry. These needs are related to the content and physical aspects of the learning media. Viewed from the aspect of content, students need learning media that is equipped with examples, exercises, and colorful pictures in it that are in accordance with the material about writing poetry. Meanwhile, the teacher's needs are, they want learning media that can attract students' interest in learning, especially writing poetry. From the results of the assessment of the feasibility of the material obtaining a score of 21. Furthermore, the results of the assessment of the linguist obtained a score of 19. The results of the assessment of the design expert obtained a score of 22. The results of the assessment of the graphic expert obtained a score of 16. Thus, the overall score obtained from the assessment of the feasibility of expert validation of 78 with the appropriate category, to become a learning media in the form of a picture book of poetry material for class VIII students of SMP Negeri 2 Baturaja.